Priests without Ordination: Catechists in Villages beyond Missions, Western Tanzania, 1948–1978 - Nyanto, Salvatory S. 19XX- (The catholic historical review, 2022)
The growth of Christianity in mid-twentieth-century western Tanzania depended on the activities of African catechists (both men and women) and teachers. These catechists lived in villages beyond the mission stations, administering catechesis to youth and adult catechumens in preparation for baptism, leading the congregation on Sunday services, and translating religious texts into the indigenous languages, to mention just a few preoccupations. Their work subsequently increased the number of Christians in village outstations (vigango). Despite their contribution to shaping the course of Christianity throughout the twentieth century, catechists have remained in the margins of the missionary enterprise, depicted simply as “examples of successful mission work.” This paper brings to prominence the hitherto-muted role of catechists in shaping the development of African Christianity in western Tanzania, in order to demonstrate that they were as important as missionaries. Furthermore, the paper intends to show that as life in villages became untenable, catechists ultimately mounted a rebellion against church authority. Nevertheless, the ideals of socialism (ujamaa), which had dominated religious and political discourse of 1960s Tanzania, divided the Catholic clergy on sustaining catechists in villages.